Theoretical Modeling of a Magnetic Loop Antenna for Ultra wide band Application - Moses Emetere (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The functionality of an improved magnetic loop antenna (MLA) is a prominent research which has span almost three decades. Its shape and size had metaphorsize from the usual analogue to a digital device-which is now used for experiments in space. In this paper, the application of MLA for ultra wide band (UWB) design was proposed. A new concept was introduced -angular displacement theory which was used to mitigate fading in multipath propagation